Evaluasi Dan Proyeksi Kebutuhan Pengembagan Terminal Penumpang Bandar Udara Internasional Sultan Syarif Kasim II Pekanbaru, Provinsi Riau Tahun 2020-2035 - Habiburrahman, Jundi; Sandhiyavitri, Ari; Djuniati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Sultan Syarif Kasim II International Airport is located in Pekanbaru City, Riau Province, has an area of the existing of 29,000 m2 with a capacity of 3.5 million passengers per year. Because passenger growth occurs every year, this will cause the passenger capacity will not be able to serve the needs of passengers in 2035. This study aims to evaluate and make projected plans for passenger terminal needs (2020-2035). The projection application uses linear regression statistical methodology. Passenger volume is used as dependent variable while the total population (Pdd) and per capita PDRB on the basis of constant prices in 2010 (Pkt) Riau Province as the independent variable with the help of SPSS version 25.00 and Microsoft Excel. Then the resulting population (Pdd) has a greater effect on the growth of domestic passengers. Based on KM Number 3 of 2008 concerning the Master Plan for the Airport (RIB) of Sultan Syarif Kasim II, it is necessary to develop this airport in the future. Based on RIB and this research, it is projected that the need for the terminal building area is 54,385 m2 (2035) with a capacity of 6.2 million passengers per year. Keywords: Evaluate, Passenger Terminal, Linier Regression, Develop